WOMEN DRIVERS IN GIG ECONOMY: WORK FLEXIBILITY AND MENTAL HEALTH TO IMPROVE JOB SATISFACTION IN PART-TIME EMPLOYEES - Isaroh, Siska Novy; Qurratu’aini, Nafia Ilhama; Boyas, Jeziano Rizkita; Sholikhah, Afifatus (Journal of Management Small and Medium Enterprises (SMEs), 2025)
The level of enthusiasm of female drivers shows that women are increasingly comfortable and confident in taking on jobs that were previously dominated by men. In this case, job flexibility has positive benefits on mental health and job satisfaction. This study aims to analyze the relationship between job flexibility, mental health, and job satisfaction among female drivers. In addition, this study will also test whether the work flexibility variable can be influenced by the mental health variable as a moderating factor. The method used in this research is quantitative with a sample of 95 female drivers, and data collection is done through distributing questionnaires online (TikTok, WhatsApp, Instagram). The results showed that work flexibility affects mental health, which in turn affects job satisfaction. Furthermore, the analysis also revealed that mental health, as a moderating variable, weakens the relationship between work flexibility and job satisfaction. Keywords: Work Flexibility; Mental Health; Job Satisfaction